2014
DOI: 10.1371/journal.pone.0093421
|View full text |Cite
|
Sign up to set email alerts
|

Floral Reward, Advertisement and Attractiveness to Honey Bees in Dioecious Salix caprea

Abstract: In dioecious, zoophilous plants potential pollinators have to be attracted to both sexes and switch between individuals of both sexes for pollination to occur. It often has been suggested that males and females require different numbers of visits for maximum reproductive success because male fertility is more likely limited by access to mates, whereas female fertility is rather limited by resource availability. According to sexual selection theory, males therefore should invest more in pollinator attraction (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 81 publications
5
46
0
Order By: Relevance
“…1a). Typically, plants with diurnal pollinators show stronger volatile emissions during the day than at night (Balao et al 2011;Borges et al 2013;Jürgens et al 2014;Morinaga et al 2009) as we observed in this study (Fig. 2), further suggesting their function in attracting day-active bee pollinators.…”
Section: Discussionsupporting
confidence: 81%
“…1a). Typically, plants with diurnal pollinators show stronger volatile emissions during the day than at night (Balao et al 2011;Borges et al 2013;Jürgens et al 2014;Morinaga et al 2009) as we observed in this study (Fig. 2), further suggesting their function in attracting day-active bee pollinators.…”
Section: Discussionsupporting
confidence: 81%
“…Sugar ratios also differed between flower sexes, with nectar of male flowers being sucrose-dominant, whereas the nectar of female flowers was hexose-dominant. Sexual differences in nectar composition have been observed in other species such as Salix myrsinifolia x phylicifolia or Salix caprea (Katoh et al 1985;Elmqvist et al 1988;Dötterl et al 2014). The consequences of such differences in sugar proportions for pollinator foraging remain to be elucidated.…”
Section: Did the Plant Species Present Valuable Resources Of Nectar?mentioning
confidence: 99%
“…The paucity of studies is surprising given the emerging consensus that herbivore populations are often as strongly controlled by predators in a top-down manner as by host plant quality via bottom-up factors (e.g., Hairston et al 1960, Oksanen et al 1981, Halaj and Wise 2001, Terborgh et al 2006. Dioecious plants express intersexual differences in several traits that are utilized by predators, not least nectar composition (Dö tterl et al 2014) and pollen availability. Differences in such plant-based resources can potentially affect both predator population dynamics (Å gren et al 2012) and their willingness to consume animal food (Stenberg et al 2011b).…”
Section: Introductionmentioning
confidence: 99%